Does foreign presence foster Islamic banks’ performance? Empirical evidence from Malaysia - Sufian, Fadzlan (Emerald, 2010)
Purpose – The paper examines the impact of entry of foreign banks on the performance of the Malaysian Islamic banking sector during the period 2001-2007. Design/methodology/approach – To maintain homogeneity, the empirical analysis is confined to two fully fledged domestic Islamic banks, three fully fledged foreign Islamic banks, 11 domestic window Islamic banks, and four foreign window Islamic banks during the period of 2001-2007. The paper applies the ordinary least square method, where the standard errors are calculated by using White’s transformation to control for cross section heteroscedasticity. Findings – The empirical findings suggest that overhead cost is negatively related to Malaysian Islamic banks’ profitability. On the other hand, Islamic banks which are better capitalized and have a higher level of liquidity tend to be more profitable. It is found that the De Novo commercial banks are relatively less profitable than their incumbent bank peers, which could be attributed to the different levels of knowledge of the market between the incumbent and the De Novo Islamic banks. Research limitations/implications – Future research could include more variables such as taxation and regulation indicators, exchange rates as well as indicators of the quality of the offered services. Another possible extension could be the examination of differences in the determinants of profitability between small and large or high and low profitability banks. In terms of methodology, a statistical cost accounting and/or frontier optimization technique, such as the non-parametric data envelopment analysis, the stochastic frontier analysis, and/or the Malmquist productivity index approach, may be adopted to examine changes in efficiency and productivity of the Malaysian Islamic banking sector. Originality/value – While extensive literature exists to examine the performance of conventional banking sectors over recent years, empirical works on the Islamic banking sector are still in its infancy. Furthermore, studies on Islamic bank performance have focused on theoretical issues and the empirical works have relied mainly on the analysis of descriptive statistics rather than rigorous statistical estimation. The paper therefore attempts to fill the gap in the literature by providing new empirical evidence on the performance of the Islamic banking sector.